Preserving Customary Law in the Era of Globalization within Indonesian Society and Legal System - Fidaus, Yuki Muhammad (Universitas Muhammadiyah Surakarta, 2024)
Globalization has significantly influenced people’s lifestyles, often leading to a shift towards more modern and contemporary cultures, which many perceive as more practical than traditional local cultures. This shift poses a challenge to the preservation of customary law, which, despite not being formally recognized by the state, continues to exist within Indonesian society. The Indonesian legal system integrates customary law as one of its key components, with the process of law enactment deeply rooted in customs derived from ancient Indonesian societal practices. The primary objective of this study is to explore the importance of maintaining customary law in the era of globalization, particularly to ensure that future generations, especially the youth, understand and appreciate their customary laws as a distinctive feature of the Indonesian state. This study employs qualitative methods, utilizing library research and data collection techniques. The findings highlight the necessity of preserving and promoting Indonesian culture and customs to safeguard them for future generations and reinforce their role as a defining characteristic of the Indonesian state. Pola hidup masyarakat dapat berubah menjadi lebih modern yang ditimbulkan oleh globalisasi. Oleh sebab itu kebudayaan baru banyak dipilih oleh masyarakat karena dinilai lebih kekinian dan praktis daripada kebudayaan adat setempat. Keberadaan hukum adat yang berada ditengah-tengah masyarakat tetap berlaku meskipun negara tidak menetapkan hukum adat tersebut. Salah satu sistem hukum Indonesia yang dianut adalah sistem hukum adat. Proses berlakunya hukum yang ada di Indonesia dipengaruhi oleh adat yang tercipta dari kebiasaan masyarakat Indonesia pada zaman dulu. Pentingnya mempertahankan hukum adat dalam era globalisasi ini bertujuan agar generasi-generasi selanjutnya khususnya generasi muda dapat memahami mengenai hukum adatnya dan sebagai ciri khas negara Indonesia. Dalam artikel ilmiah ini menggunakan metode kualitatif dengan cara teknik pengumpulan studi pustaka. Kita harus selalu melestarikan dan mengupayakan untuk mempertahankan budaya dan adat Indonesia untuk generasi generasi selanjutnya dan sebagai ciri khas dari negara Indonesia.